Blue cooperative luminescence in Yb3+-doped tellurite glasses excited at 1.064 mu m - dos Santos, P. V.; Vermelho, MVD; Gouveia, E. A.; de Araujo, M. T.; Gouveia-Neto, A. S.; Cassanjes, F. C.; Ribeiro, SJL; Messaddeq, Younes [UNESP] (American Institute of Physics (AIP), 2002)
Blue luminescence emission around 480 nm through cooperative upconversion from pairs of Yb3+ ions implanted into 60TeO(2)-10GeO(2)-10K(2)O-10Li(2)O-10Nb(2)O(5) tellurite glasses and excited by a cw laser at 1.064 mum is demonstrated. Cooperative luminescence emission enhancement owing to the temperature dependent multiphonon-assisted anti-Stokes excitation process of the ytterbium ions is also observed. The experimental results revealed a fourfold enhancement in the cooperative luminescence emission when the sample was heated in the temperature range of 20 degreesC-260 degreesC. The thermally induced enhancement is assigned to the effective absorption cross-section for the ytterbium ions which is an increasing function of the medium temperature. (C) 2002 American Institute of Physics.